Between God and Hitler: military chaplains in Nazi Germany - Bergen, Doris L. (Cambridge University Press, 2023)
During the Second World War, approximately 1000 Christian chaplains accompanied Wehrmacht forces wherever they went, from Poland to France, Greece, North Africa, and the Soviet Union. Chaplains were witnesses to atrocity and by their presence helped normalize extreme violence and legitimate its perpetrators. Military chaplains played a key role in propagating a narrative of righteousness that erased Germany's victims and transformed the aggressors into noble figures who suffered but triumphed over their foes. Between God and Hitler is the first book to examine Protestant and Catholic military chaplains in Germany from Hitler's rise to power, to defeat, collapse, and Allied occupation. Drawing on a wide array of sources - chaplains' letters and memoirs, military reports, Jewish testimonies, photographs, and popular culture - this book offers insight into how Christian clergy served the cause of genocide, sometimes eagerly, sometimes reluctantly, even unknowingly, but always loyally.